(untitled) (Scientific journal of the Fergana State University, 2023)
Nowadays there are a huge number of techniques designed for the development of language skills, but it is also very important to develop students’ critical thinking in order to prepare them for adulthood. This article discusses various techniques for developing students’ critical thinking through the study of proverbs and sayings, and also analyzes the effectiveness of their use in English lessons